Stressors and difficulties perceived during the pandemic in the teaching activity of nursing professors - Losa-Iglesias, Marta; Jimenez-Fernandez, Raquel; Corral-Liria, Inmaculada; Herraiz-Soria, Elena; Rodriguez-Vazquez, Rocio; Becerro-De-Bengoa-Vallejo, Ricardo (Frontiers in Psychology, 2022)
Background The coronavirus 2019 (COVID-19) pandemic has prompted several changes in teaching methods in addition to the ways of learning by students. Objective To check whether a relationship between factors, such as resilience, self-esteem, depression, anxiety, and academic stressors, and a change in teaching methods and learning since the first epidemic outbreak exists. Methods This study was a cross-sectional descriptive one with a non-random sample of nursing degree teachers who did or did not participate in clinical activities but had been teaching online since the start of the pandemic. Data were collected with online questionnaires validated for self-completion with Google Forms. Results Regarding the analysis of the descriptive data of each scale, we can verify that data indicate very high levels of resilience and self-esteem in normal range with minimal levels of depression, moderate anxiety and finally not worrying about sources of stress in teachers. Also, negative correlations were found between the 10 CONNOR–DAVIDSON RESILIENCE scale, BECK DEPRESSION INVENTORY (BDI 2), BECK ANXIETY INVENTORY (BAI) and SCALE OF SOURCES OF STRESS IN TEACHERS with a statistical significance of p < .001. The ROSENBERG SELF-ESTEEM scale, which also showed negative correlations with the three previously mentioned scales with a statistical significance of p <0.001. Finally, positive correlations between the BECK (BDI 2), BECK (BAI), and SOURCES OF STRESS IN TEACHERS scales and between the ROSENBERG SELF-ESTEEM scale and the 10 CD RISC scale were found (p < .001). Discussion Our study shows that nursing degree teachers combine teaching with activities and presented moderate levels of anxiety, depression, and tolerance to academic stressors and were able to maintain optimal levels of self-esteem and resilience, indicating that these two factors act as protectors against these stressors.